Edukasi Usaha Budidaya Cacing Tubifex sebagai Salah Satu Peluang Ekonomi bagi Masyarakat Desa Lubuk Saban Kecamatan Pantai Cermin Kabupaten Serdang Bedagai - Emmy Syafitri; Dwi Tika Afriani; Mekar Meilisa Amalia (Jurnal Pengabdian Pada Masyarakat, 2020)
THE EDUCATION OF TUBIFEX WORM CULTIVATION BUSINESS AS ONE OF THE ECONOMIC OPPORTUNITIES FOR PEOPLE OF LUBUK SABAN VILLAGE, PANTAI CEMIN DITRICT, SERDANG BEDAGAI REGENCY. Lubuk Saban is one of the areas whose population is engaged in aquaculture businesses where a large supply of freshwater fish is needed. Most farmers use artificial pellets which are relatively expensive, while the production cost can be reduced using natural food. Besides being cheaper, natural feed such as Tubifex are environmentally friendly. The purpose of this community service activity is to enable freshwater fish farmers in Lubuk Saban Village gain knowledge of Tubifex worm cultivation as one of the natural feed substitutes. In addition, this activity is expected to help the community in opening new business opportunities, provide natural food, reduce production costs, and improve the community's economy. The implementation of service activities is carried out using counseling methods with material exposure activities and direct practice regarding the stages of this Tubifex cultivation, with questionnaires and interactive discussions between devotees and students. From the results of community service activities conducted, it is concluded that participants of the service received new knowledge on the cultivation of Tubifex worms as one of the very promising economic opportunities. Furthermore, the servants gained field knowledge and new experiences on how to approach the general public, especially freshwater fish farmers